Analisis program GLS (gerakan literasi sekolah) pada tahap pembiasaan di sekolah dasar - Salma Fitriati; Seni Apriliya; Nana Ganda (IKIP Siliwangi, 2024)
AbstractResponding to the low literacy culture based on research which states that literacy skills in Indonesia are still lacking and lagging behind, the government held the GLS (School Literacy Movement) program as an effort to increase literacy culture. GLS (School Literacy Movement) activities in elementary schools at the habituation stage are the habit of reading 15 minutes before learning. This study aims to describe and pay attention to the implementation and overall support of GLS (School Literacy Movement) in one of the elementary schools in Tasikmalaya. The approach used in this study is descriptive qualitative using data collection techniques through interviews, observation, and documentation. The results of this study indicate that the implementation of the GLS (School Literacy Movement) in elementary schools was carried out based on indicators of achievement of the GLS program at the habituation stage before the Covid-19 pandemic, especially during the WJLRC (West Java Leader's Reading Challenge) program. Meanwhile, after the Covid-19 pandemic, GLS activities were carried out but not optimal with the damage to various facilities that were not maintained and the lack of programs from the government that could stimulate GLS (School Literacy Movement). Thus, a program that can stimulate the movement of the GLS (School Literacy Movement) program at the habituation stage should be held again in order to revive the GLS (School Literacy Movement) program which has hardly been cultivated in elementary schools. Keywords: GLS’s Program, Elementary school, Habituation Stage. AbstrakMerespon rendahnya budaya literasi berdasarkan riset yang menyebutkan bahwa kemampuan literasi di Indonesia masih kurang dan tertinggal, pemerintah mengadakan program GLS (Gerakan Literasi Sekolah) sebagai upaya peningkatan budaya literasi. Kegiatan GLS (Gerakan Literasi Sekolah) di sekolah dasar pada tahap pembiasaan berupa pembiasaan membaca 15 menit sebelum pembelajaran.. Penelitian ini bertujuan untuk mendeskripsikan dan memperhatikan pelaksanaan dan keseluruhan penunjang GLS (Gerakan Literasi Sekolah) di salah satu sekolah dasar yang ada di Tasikmalaya. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif deskriptif dengan menggunakan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil dari penelitian ini menunjukkan bahwa pelaksanaan GLS (Gerakan Literasi Sekolah) di Sekolah dasar terlaksana berdasarkan indikator pencapaian program GLS pada tahap pembiasaan pada saat sebelum pandemi Covid-19 terutama saat adanya program WJLRC (West Java Leader’s Reading Challenge). Sedangkan pada saat setelah pandemic Covid-19 kegiatan GLS telaksana namun tidak optimal dengan rusaknya berbagai fasilitas yang tak terawatt dan kurangnya program dari pemerintah yang dapat menstimulasi GLS (Gerakan Literasi Sekolah). Sehingga, adanya program yang dapat menstimulasi bergeraknya program GLS (Gerakan Literasi Sekolah) pada tahap pembiasaan sebaiknya diadakan kembali guna menghidupkan program GLS (Gerakan Literasi Sekolah) yang sudah hampir tidak dibudayakan di sekolah dasar. Kata Kunci: Program GLS, Sekolah Dasar, Tahap Pembiasaan.